On the semantics of modal particle de in mandarin chinese - Xie, Zhiguo (Proceedings of the Amsterdam Colloquium, 2007)
I argue that the Mandarin modal particle de has a temporal presupposition in its ability and epistemic semantics. Hence the two uses are incompatible with past-denoting time adverbials. Elements like the contrastive focus marker hai ‘still’ have a temporal shifting property and can license past-denoting adverbials in modal de-sentences.